Usage Of Edible Coating To Improve The Quality And Shelf Life Of Tomato (Solanum Lycopersicum) - Hormat, Nurhuda (Universiti Sains Malaysia, 2020)
Tomatoes are commercially perishable fruit within a short period of time because they contain high moisture content, thus longer shelf life is needed for better marketing and fulfil consumer satisfaction. Edible coating is one of the most effective way to slow down the process of fruit maturity and polysaccharides as edible coating, has been found to improve the shelf life and quality of fruits and vegetables. The aim of this research is to determine the influence of different types of edible coating which are alginate, pectin and a mixture of both pectin and alginate in extending the shelf-life of tomato by (i) evaluate the effectiveness of coating in improving the physicochemical characteristics of tomato by using physical and chemical analysis and (ii) evaluate the shelf life of coated tomato using different types of coating by using microbiological analysis. Tomatoes were coated with different coating and stored at a ±10 °C. Several physicochemical and microbiological analysis such as physiological weight loss, pH, titratable acidity (TA), total soluble solid (TSS), total colour change, total aerobic mesophilic count and total yeast and mold were performed. The result showed that tomatoes with coating has delayed ripening process with better quality than the uncoated ones. Sample coated with pectin coating could retard the moisture loss and, thus, reduce the physiological weight loss in tomato while alginate coating showed a positive effect in lowering down the appearance of red colour on tomato during storage. Furthermore, sample coated with pectin+ alginate showed a positive effect in retarding the ripening process of tomato by reduce the pH value of tomato that expected to be increase with advancement of ripening stages.